Assessment of a digital and an analog PET/CT system for accurate myocardial perfusion imaging with a flow phantom - Siekkinen Reetta; Kirjavainen Anna K; Koskensalo Kalle; Smith Nadia AS; Fenwick Andrew; Saunavaara Virva; Tolvanen Tuula; Iida Hidehiro; Saraste Antti; Teräs Mika; Teuho Jarmo (Springer, 2022)
In Myocardial Perfusion Imaging (MPI) with Positron Emission Tomography/Computed Tomography (PET/CT) systems, accurate quantification is essential. We assessed flow quantification accuracy over various injected activities using a flow phantom.Methods The study was performed on the digital 4-ring Discovery MI (DMI-20) and analog Discovery 690 (D690) PET/CT systems, using 325-1257 MBq of [O-15]H2O. PET performance and flow quantification accuracy were assessed in terms of count-rates, dead-time factors (DTF), scatter fractions (SF), time-activity curves (TACs), areas-under-the-curves (AUCs) and flow values.Results On DMI-20, prompts of 12.8 Mcps, DTF of 2.06 and SF of 46.1% were measured with 1257 MBq of activity. On the D690, prompts of 6.85 Mcps, DTF of 1.57 and SF of 32.5% were measured with 1230 MBq of activity. AUC values were linear over all activities. Mean wash-in flow error was - 9% for both systems whereas wash-out flow error was - 5% and - 6% for DMI-20 and D690. With the highest activity, wash-out flow error was - 12% and - 7% for the DMI-20 and D690.Conclusion DMI-20 and D690 preserved accurate flow quantification over all injected activities, with maximum error of - 12%. In the future, flow quantification accuracy over the activities and count-rates evaluated in this study should be assessed.